Effects of Covid-19 Outbreaks on Demand for Electronic News in New Bussa, Nigeria - Eric Irunokhai; Joseph Adigun; Oluwafemi Adeniji; Yusuf Sada; David Oyeleye; Yetunde Areo; John Onihunwa (Covenant Journal of Communication, 2021)
The work investigates how the Covid-19 outbreak affects the demand for electronic news before and during the lockdown in New Bussa, a major town in Niger State, one of Nigeria’s 36 political subdivisions. It also explores the adoption of social media channels in disseminating news related to the pandemic. The questionnaire on Google form was distributed to the residents of the town to which 150 of them responded. The results,among others, show that even though there was a higher demand for news in the thick of the pandemic, it was not significant. This outcome does not align with the previous findings that found demand significantly risen in a similar situation. What is more, this finding brings a rethinking of the classical conditioning theory to the table.